2006
DOI: 10.1242/dev.02293
|View full text |Cite
|
Sign up to set email alerts
|

Roles for Dnmt3b in mammalian development: a mouse model for the ICF syndrome

Abstract: ICF (Immunodeficiency, Centromeric instability and Facial anomalies) syndrome is a rare autosomal recessive disease caused by mutations in the DNA methyltransferase gene DNMT3B. To investigate the function of Dnmt3b in mouse development and to create animal models for ICF syndrome, we have generated three mutant alleles of Dnmt3b in mice: one carrying a deletion of the catalytic domain (null allele) and two carrying ICF-like missense mutations in the catalytic domain. The Dnmt3b null allele results in embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
125
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 45 publications
8
125
1
1
Order By: Relevance
“…The Dnmt3b hypomorphic mutant mice we generated exhibit growth defects, skull anomalies, high rate of mortality at birth, and hypomethylation of minor satellite sequences, similar to what was observed in a previously described mouse model (40). However, a deeper analysis of the skeleton revealed severe skull defects and posterior homeotic transformations that often reflect Hox genes deregulation (33).…”
Section: Discussionsupporting
confidence: 79%
“…The Dnmt3b hypomorphic mutant mice we generated exhibit growth defects, skull anomalies, high rate of mortality at birth, and hypomethylation of minor satellite sequences, similar to what was observed in a previously described mouse model (40). However, a deeper analysis of the skeleton revealed severe skull defects and posterior homeotic transformations that often reflect Hox genes deregulation (33).…”
Section: Discussionsupporting
confidence: 79%
“…Dnmt3b deficiency results in embryonic lethality in mice aged E14.5-E16.5, with multiple tissue defects including ventricular septal defect. 21 In agreement, congenital heart defects were also observed in three patients with DNMT3B mutations. Furthermore, two ICF2 patients carrying mutations in ZBTB24 had a cardiac defect, suggesting the effects of this gene on embryonic development.…”
Section: Discussionsupporting
confidence: 58%
“…Flowcytometric analysis of CD4, CD8 and TCRb expression revealed no developmental defect of the T-cells in the thymus of newborn mice. 21 Likewise, in young ICF patients, the numbers of CD3 ĂŸ T-cells, CD4 ĂŸ and CD8 ĂŸ T-cell subsets are normal, irrespective of the group. However, in vitro stimulation of PBMCs with PHA/IL-2 and irradiated allogeneic feeders revealed that the expansion of T-cells was reduced in all ICF1 and ICF2 cases investigated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with a rare autosomal recessive syndrome, the immunodeficiency, centromere instability, facial anomalies (ICF) syndrome, have germline mutations in the DNMT3B gene (Hansen et al, 1999;Xu et al, 1999;Shirohzu et al, 2002), and lymphocytes from affected individuals display hypomethylation of repetitive DNA sequences. Furthermore, mice expressing Dnmt3b alleles similar to those found in ICF syndrome are small with abnormal craniofacial development and hypomethylation of repetitive elements, suggesting that these alleles encode hypomorphic proteins (Ueda et al, 2006).…”
Section: Introductionmentioning
confidence: 95%